Bivariate Legendre approximation - Zerroug, Abdelhamid; Sehili, Ismahene (International Journal of Applied Mathematical Research, 2017)
Spectral methods are among the numerical methods commonly used for approximating solutions of boundary value problems. In this paper we propose, a generalization of the spectral Tau method in dimension 2, this method is generalized by the use of a new two-dimensional polynomial basis constructed byÂ  aÂ  three terms recurrence relation. We also present an estimation of error committed by the proposed method.